Pengaruh Konten Unboxing dan Review Affiliator Tiktok Shop terhadap Minat Beli Produk Fashion Mahasiswa Perbankan Syariah IPMAFA - Zyayan Afiana; Ahmad Dimyati (JIOSE: Journal of Indonesian Sharia Economics, 2026)
The digitalization of the economic sector has driven the emergence of various innovations, one of which is e-commerce platforms such as TikTok Shop, which are widely favored by Generation Z, including students of the Islamic Banking Study Program at IPMAFA. Common marketing strategies used on this platform include unboxing content and affiliate reviews that leverage the For You Page (FYP) feature, particularly for trending fashion products. This study aims to analyze the effect of unboxing content and affiliate reviews on students’ purchase intention. The research employs a quantitative method with a simple random sampling technique, resulting in 69 samples drawn from a total population of 83 respondents using the Slovin formula. Data analysis was conducted using SmartPLS 3.2.9. The results indicate that unboxing content does not have a significant effect on purchase intention, while affiliate reviews have a positive and significant effect, with a t-statistic value of 4.914 (> 1.99495). Simultaneously, unboxing content and affiliate reviews have a positive and significant effect on purchase intention, contributing 38% to the variance.